Generations of freedom : gender, movement, and violence in Natchez, 1779-1865 - Ribianszky, Nik (Early American places., 2021)
"In Generations of Freedom: Gender, Movement, and Violence in Natchez, 1779-1865, Nik Ribianszky employs the lenses of gender and violence to examine family, community, and the tenacious struggles by which free Blacks claimed and maintained their freedom under shifting international governance, from Spanish colonial rule (1779-1795), through American acquisition (1795) and eventual statehood (established in 1817), and finally to slavery's legal demise in 1865"--